Multiple SARS-CoV-2 Variants Exhibit Variable Target Cell Infectivity and Ability to Evade Antibody Neutralization - Tang, Haijun; Gao, Long; Wu, Zhao; Meng, Fang; Zhao, Xin; Shao, Yun; Hou, Guocun; Du, Xiaohong; Qin, F. Xiao-Feng (Frontiers in Immunology, 2022)
The continuous emergence of SARS-coronavirus 2 (SARS-CoV-2) variants, especially the variants of concern (VOC), exacerbated the impact of coronavirus disease 2019 (COVID-19) pandemic. As the key of viral entry into host cells, the spike (S) protein is the major target of therapeutic monoclonal antibodies (mAbs) and polyclonal antibodies elicited by infection or vaccination. However, the mutations of S protein in variants may change the infectivity and antigenicity of SARS-CoV-2, leading to the immune escape from those neutralizing antibodies. To characterize the mutations of S protein in newly emerging variants, the proteolytic property and binding affinity with receptor was assessed, and the vesicular stomatitis virus (VSV)-based pseudovirus system was used to assess the infectivity and immune escape. We found that some SARS-CoV-2 variants have changed significantly in viral infectivity, especially, B.1.617.2 is more likely to infect less susceptible cells than D614G, and the virus infection process can be completed in a shorter time. In addition, neutralizing mAbs and vaccinated sera partially or completely failed to inhibit entry mediated by the S protein of certain SARS-CoV-2 variants. However, SARS-CoV-2 variants S protein mediated viral infection can be blocked by protease inhibitors and endocytosis inhibitors. This work provides deeper understanding of the rise and evolution of SARS-CoV-2 variants and their immune evasion.